Praying for a Miracle: Negative or Positive Impacts on Health Care? - Leal, Miriam Martins; Nwora, Emmanuel Ifeka; de Melo, Gislane Ferreira; Freitas, Marta Helena (Frontiers in Psychology, 2022)
The belief in miracle, as a modality of spiritual/religious coping (SRC) strategy in the face of stress and psychic suffering, has been discussed in psychological literature with regard to its positive or negative role on the health and wellbeing of patients and family members. In contemporary times, where pseudo conflicts between religion and science should have been long overcome, there is still some tendency of interpreting belief in miracle as having unhealthy impacts in the care and treatment of health. This position seeks to find a base in three characteristics of hope in miracle, frequently pointed out by psychological literature: a) it would imply a negation of reality instead of its direct confrontation; b) it would be a coping strategy focused on emotion instead of the problem; c) it would imply seeking to modify the supposed desire of God by extra natural facts. In this paper we shall critically discuss this position and the dangers of its crystallization by the use of SRC scales in which the act of praying for a miracle is previously classified as a negative strategy. We revisit some tendencies in psychological literature about the subject, taking into consideration the various facets of miracle, sociocultural facts, elements of idiographic nature and their profound outcomes in the life world of people especially in health contexts. We illustrate the dangers of a hasty generalization of the results of nomothetic studies about the role of belief in miracle with two examples of research in Brazilian context: one carried out with pregnant women with fetal malformation and the other with family members caring for children and adolescents with cancer under chemotherapeutic treatment. In both studies the results found do not confirm predominance of negative aspects associated with the act of praying for a miracle, which we discuss and analyze in light of the phenomenological perspective. In this perspective, “pray for a miracle” as experienced by patients and caregivers, can be recognized as an act of openness to life (instead of isolation in a bleak perspective), bolstering hope and resignification of reality in the psyche.